Impurity removal from petroleum coke - Gagnon, A.; Backhouse, N.; Darmstadt, H.; Ryan, E.; Dyer, Laurence; Dixon, D. (2016)
© The Minerals, Metals & Materials Society 2016. The question of treating high-impurity coke to enable use in anodes was examined. A mineralogical analysis of different cokes demonstrated that more than 99 % of the particles contained the expected concentrations of sulfur, nickel, and vanadium while a small number of particles contained inclusions of other impurities. A number of potential treatment options were identified and investigated, with thermal desulfurization being studied further. The initial sulfur concentration, residence time and calcination temperature had the highest influence. 45 % sulfur removal was achieved but with significant bulk density loss. Acceptable pilot anode quality was not achievable even with the fines fraction substituted with desulfurized material. Therefore while sulfur removal during calcining is possible, the resulting coke, even in the most promising scenario, is not suitable for anode manufacturing. At this time, an industrial process to remove sulfur and other impurities from petroleum coke is unlikely to be viable.